Peg-in-hole operation with a cobot without using external sensors. (2018) - Seriani, Stefano; D'Attanasio, Simona; Gallina, Paolo; Debortoli, Luca
Abstract: Collaborative robots, or cobots, are designed to interact with humans and to be easy to use, drastically reducing the integration costs. In this paper, we present the results of a peg-in-hole operation, performed by an UR5 cobot equipped with a standard gripper, without the use of external force or torque sensors. The operation consists of the insertion of a 48-tooth involute spline shaft in a corresponding hub. A two-phase helicoidal descent is performed by the robot. During the first phase, the value of the force vector at the tool center point is used to detect if the shaft is centered. During the second phase, the variation of the torque at shoulder joint is used to detect the insertion. Over 1000 peg-in-hole operations, the successful rate was 96.7%. Among these shafts, only the 10% needed a second trial. The overall mean time for an operation is 5.5 seconds.